Differential diagnosis and treatment infertility with hyperprolactinemia - T V Ovsyannikova (IP Berlin A.V., 2014)
Nfertility in hyperprolactinemia is one of the most frequent causes of treatment of women in the gynecological clinic. Hyperprolactinemia, amenorrhea and menstrual disorders by type of anovulation with/without prolaсtinomаs inherent in this group of patients. Restoration of menstrual and reproductive functions may drugs bromocriptine or cabergoline derivates.